Brainstem auditory evoked responses and bone conduction assessment in alpacas. (May 2021) - Aleman, M.; Crowe, C.; Dechant, J.; Bellone, R.R.; Avila, F.
Abstract: Auditory loss has been reported in camelids using brainstem auditory evoked responses (BAER). Differentiation between conductive versus sensorineural dysfunction has not been investigated. Therefore, the objective of the study was to investigate auditory function using BAER and bone conduction (BC). Twenty-four alpacas: 15 females, 9 intact males (2–16 years of age) were included in a randomized clinical trial. BAER and BC were recorded using two derivations (vertex to mastoid and vertex to cranial aspect of second cervical vertebra). All alpacas underwent complete physical examinations and were sedated with xylazine hydrochloride at 0.6 mg/kg IM. Peaks, when present, were identified and latencies, amplitudes, and amplitude ratios were determined. Eleven alpacas had normal responses and 13 had auditory loss based on BAER. The latter consisted of complete absence of peaks bilaterally ( n  = 3), absence of peaks unilaterally ( n  = 1), delayed latencies bilaterally ( n  = 4), and delayed latencies unilaterally ( n  = 5). Distinct peaks on BC supported conductive auditory loss in 6 alpacas, difficult to interpret due to stimulus artifact and additional undefined peaks in 4, and absent peaks in 3 alpacas. The cause of auditory loss was presumed to be due to otitis in 6, aging in 4 (10–16 years old), and congenital sensorineural (absent peaks on BAER and BC) in 3 alpacas with unpigmented fiber and irises. BAER and BC are useful and non-invasive to perform techniques for the investigation of auditory loss in alpacas, and further characterization as conductive or sensorineural. Highlights: Brainstem auditory evoked responses and bone conduction were used to investigate auditory function in camelids Results highlight the importance to determine types of auditory loss (sensorineural versus conductive). Accurate determination of type of auditory loss is essential for proper characterization of phenotype required for genetic studies. Both techniques are non-invasive, safe, easy to perform, and well tolerated.